Intraseasonal climate forecast of iba tropical cyclone in northeast Brazil using the regional climate model - a case study - Corrêa, Cleber Souza; Camillo, Gerson Luiz (Ciência e Natura, 2022)
This study aimed to analyze the operationally stored simulations of the RegCM4.7 model using simulations performed by the National Center for Environmental Prediction (NCEP) coupled forecast system model version 2 (CFSv2) in downscaling. The South American domain, however, seeks to observe prevailing weather systems that may affect the Alcântara Rocket Launch Center in Maranhão. One case is analyzed with three different global initializations of the CFSv2 model. On March 25, 2019, the occurrence of Cyclone Iba on the southern coast of Bahia. The RegCM4.7 Regional Model was able to simulate tropical cyclone three months in advance. This performance is very important because the influence of these anomalous systems affect wind intensity and rainfall behavior in the Alcântara region because it would affect the convective processes on the continent in northeastern Brazil.